PROC report by example : techniques for building professional reports using SAS (SAS Institute, 2013)
PROC REPORT by Example: Techniques for Building Professional Reports Using SAS provides real-world examples using PROC REPORT to create a wide variety of professional reports. Written from the point of view of the programmer who produces the reports, this book explains and illustrates creative techniques used to achieve the desired results. Each chapter focuses on a different concrete example, shows an image of the final report, and then takes you through the process of creating that report. You will be able to break each report down to find out how it was produced, including any data manipulation you have to do. The book clarifies solutions to common, everyday programming challenges and typical daily tasks that programmers encounter. For example: * obtaining desired report formats using style templates supplied by SAS and PROC TEMPLATE, PROC REPORT STYLE options, and COMPUTE block features * employing different usage options (DISPLAY, ORDER, GROUP, ANALYSIS, COMPUTED) to create a variety of detail and summary reports * using BREAK statements and COMPUTE blocks to summarize and report key findings * producing reports in various Output Delivery System (ODS) destinations including RTF, PDF, XML, TAGSETS. RTF * embedding images in a report and combining graphical and tabular data with SAS 9.2 and beyond Applicable to SAS users from all disciplines, the real-life scenarios will help elevate your reporting skills learned from other books to the next level. With PROC REPORT by Example: Techniques for Building Professional Reports Using SAS what seemed complex will become a matter of practice.